Botulinum Toxin Injections as a Treatment of Postoperative Chronic Neck Pain Secondary to Cervical Spine Surgery - Meiling, James; Barndt, Brandon; Raum, George; Schulze, David (Indian Journal of Neurosurgery, 2020)
Postoperative neck pain is a relatively common consequence of cervical spine surgeries such as anterior cervical discectomy with fusion and laminoplasty. Botulinum toxin injections are a relatively new treatment option to target muscle spasms, a possible cause of postoperative neck pain. This systematic review aims to evaluate the current literature highlighting the utilization of botulinum toxin for treating postoperative neck pain. The literature search resulted in one preliminary case–control trial, one case series and one case report. The use of Botox in these studies had promising benefits on postoperative neck pain, by reducing visual analog scores and improving objective measures of muscle tone such as cervical lordosis angle. While not seen in these studies, the use of botulinum toxin injections into the muscles of the region of the head, neck, and shoulder is not without risks such as focal muscle loss, joint instability, and respiratory and swallowing difficulty. With this in mind, while botulinum toxin may be a promising treatment for these patients, further well-designed studies are needed to further assess the treatments efficacy and safety in this patient population.
Keywords: postoperative neck pain; botulinum toxin; cervical spine surgery